RAFT polymerization of ciprofloxacin prodrug monomers for the controlled intracellular delivery of antibiotics. Issue 4 (8th December 2015) - Das, Debobrato; Srinivasan, Selvi; Kelly, Abby M.; Chiu, David Y.; Daugherty, Bridget K.; Ratner, Daniel M.; Stayton, Patrick S.; Convertine, Anthony J.
Abstract : Prodrug monomers derived from the antibiotic ciprofloxacin were synthesized with phenolic or aliphatic esters linking the drug to a polymerizable methacrylate group. Abstract : Prodrug monomers derived from the antibiotic ciprofloxacin were synthesized with phenolic or aliphatic esters linking the drug to a polymerizable methacrylate group. RAFT polymerization of these monomers exhibited linear pseudo-first-order kinetics and M n vs. conversion plots, and low Đ values throughout the polymerization. Prodrug monomers were then copolymerized with polyethyleneglycol methacrylate to yield hydrophilic copolymers with narrow Đ values. A poly(O950) macroCTA was also synthesized and chain extended with the antibiotic monomers to form diblock copolymers. The resultant copolymers and diblock copolymers were characterized with 1 H and 19 F NMR and found to contain 16.5 and 30–35 wt% ciprofloxacin, respectively. DLS measurements demonstrated that the copolymers remained unimeric between pH 5.6–7.4, while the diblock copolymers formed nanoparticles with diameters between 30–40 nm at physiological pH. Drug release kinetics were measured in human serum via HPLC analysis. Copolymers containing ciprofloxacin linked via phenolic esters showed faster hydrolysis rates with 50% drug released at 120 h, whereas copolymers with the corresponding aliphatic ester linkages showed the same drug release over 22 d. Diblock copolymers with a discrete ciprofloxacin block and a poly(O950) stabilizing block self-assembled into micelles, and exhibited reduced hydrolysis rates for both ester linked drugs. In vitro toxicity measurements in RAW 264.7 cells showed the copolymers to be nontoxic up to 20 mg mL −1 following a 24 h incubation period. The polymer drugs were shown to be active against Burkholderia thailandensis in a bacteria-macrophage co-culture model of melioidosis with MIC values of 6.0 and 0.6 mM for the aliphatic and phenyl ester linked copolymeric prodrugs, respectively.